1994
DOI: 10.1007/bf01808619
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic lesion of the trigeminal nucleus caudalis for deafferentation facial pain

Abstract: The deafferentation facial pain syndrome, caused by physical, herpetic or tumourous lesions of the trigeminal sensory root, was successfully managed with ultrasonic trigeminal nucleotomy. The article presents this new surgical technique and its results in 14 patients suffering from severe facial pain and dysaesthesias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Surgical alternatives to extend the duration of relief, such as stereotactic radiosurgical treatment of SPG neuralgia, have also been reported 14 . Ipsilateral facial paresis following ultrasonic lesioning of the trigeminal nucleus caudalis for deafferentation facial pain has been reported 15 …”
Section: Discussionmentioning
confidence: 99%
“…Surgical alternatives to extend the duration of relief, such as stereotactic radiosurgical treatment of SPG neuralgia, have also been reported 14 . Ipsilateral facial paresis following ultrasonic lesioning of the trigeminal nucleus caudalis for deafferentation facial pain has been reported 15 …”
Section: Discussionmentioning
confidence: 99%
“…Instead, a series of lesions are made below the level of the fourth ventricle and extending to the C 2 dorsal nerve roots. Many variations of the DREZ lesioning technique have since been used, including using laser[16] energy, using ultrasonic energy,[9] and broadening the nucleus caudalis lesion width by using a double-row of lesions. [24] Kanpolat innovated a CT guided percutaneous technique for single nucleotomy lesion placement.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, complications were mostly major; Hitchcock et al [38] reported at least one of the following complications in all three patients (100%) including ipsilateral facial and contralateral arm and body sensory loss. Also, the study by Grigoryan et al [35] which used ultrasonic nucleus caudalis destruction reported complications in 75% (3/4) of patients including contralateral body sensory loss, ataxia and Brown-Sequard syndrome. Chivukula et al [23] reported one incidence of neuropathy/radiculopathy among the three patients who had caudalis DREZ lesioning.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies comprising 63 patients with resistant trigeminal PHN to medical therapy were identified from the literature review [23, 35-38]. Four studies performed caudalis DREZ lesioning/stereotactic nucleotomy-nucleotractotomy using a radiofrequency generator, and 1 study performed ultrasonic destruction of the nucleus caudalis 4 months to 4.5 years following zoster onset.…”
Section: Resultsmentioning
confidence: 99%